ENTERPRISE AS AN OBJECT OF MANAGEMENT: CURRENT PROBLEMS, EVOLUTION OF A HARMONIOUS APPROACH, HARMONY OF INTERESTS - M. P. Kalinichenko (Вестник университета)
A synthetic understanding of the essence of the enterprise as an object of management has been formed based on the historical method and determinism between the evolution of the paradigms of economic theory and the evolution of the theory of the company. It has been proved that the subject of the theory of the company should be based on economic interests. The nature, boundaries and development factors of the company should be analysed and explained on the basis of the manifestation and interaction of interests and, as a consequence, emerging economic relations. The evolution of a harmonious approach to management the essence of which is the formation of an integrated enterprise management system, consolidated by common interests, universal values, integration of strategies, functions and processes, – has been presented.